2007
DOI: 10.1007/s11064-007-9430-x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Environmentally Relevant Polybrominated Diphenyl Ether (PBDE) Congeners on Calcium Buffering Mechanisms in Rat Brain

Abstract: Polybrominated diphenyl ethers (PBDEs) are widely used as additive flame-retardants and have been detected in human blood, adipose tissue, and breast milk. Developmental and long-term exposures to these chemicals may pose a human health risk, especially to children. We have previously demonstrated that polychlorinated biphenyls (PCBs), which are structurally similar to PBDEs and cause neurotoxicity, perturb intracellular signaling events including calcium homeostasis and protein kinase C translocation, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 71 publications
(115 reference statements)
1
38
0
Order By: Relevance
“…Similar results were also obtained with BDE-47 in mouse cerebellar granule neurons (Costa, Tagliaferri, et al, unpublished). Kodavanti and Ward (2005) later showed that DE-71 (8–22 μM) inhibited Ca 2+ uptake in microsomes, and particularly in mitochondria isolated from rat brain, and Coburn et al (2008) confirmed these findings with BDE-47 and BDE-99.…”
Section: Potential Mechanisms Of Pbde Developmental Neurotoxicitymentioning
confidence: 70%
“…Similar results were also obtained with BDE-47 in mouse cerebellar granule neurons (Costa, Tagliaferri, et al, unpublished). Kodavanti and Ward (2005) later showed that DE-71 (8–22 μM) inhibited Ca 2+ uptake in microsomes, and particularly in mitochondria isolated from rat brain, and Coburn et al (2008) confirmed these findings with BDE-47 and BDE-99.…”
Section: Potential Mechanisms Of Pbde Developmental Neurotoxicitymentioning
confidence: 70%
“…The role of mitochondria as Ca 2+ -buffering systems has been demonstrated in several models by many studies (see for example [42,43]). Furthermore, this was shown to be true also for retinal cells, especially for amacrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…BDE-47 induced oxidative stress in hippocampal neurons in parallel to a reduced expression level of antioxidative proteins and enzymes (GSH, SOD, GSH-Px), which might lead to induction of apoptosis (He et al, 2008a). In addition, alterations in calcium homeostasis were observed in mitochondria prepared from rat brain (Coburn et al, 2008) and SHSY5Y cells (He et al, 2009b). …”
Section: Neurotoxicitymentioning
confidence: 99%
“…Cytotoxicity as measured by MTT reduction was detected in the neuroblastoma cell line SK-N-MC (Tagliaferri et al, 2010) and the human astrocytoma cell line (132-1N1) (Madia et al, 2004). In addition, alterations in neural migration/differentiation of human neural progenitor cells (Schreiber et al, 2010) and modulations of calcium uptake determined in rat mitochondria (Coburn et al, 2008) have been reported. Large-scale proteomic analyses with non-toxic and cytotoxic concentrations showed that BDE-99 alters the expression of cytoskeletal proteins already at low concentrations in cerebellar cortical cells isolated from rat fetuses on GD21 (Sprague-Dawley rats).…”
Section: Neurotoxicitymentioning
confidence: 99%